Synergistic Effect on Neurodegeneration by N-Truncated Aβ4−42 and Pyroglutamate Aβ3−42 in a Mouse Model of Alzheimer's Disease - Lopez-Noguerola, Jose S.; Giessen, Nicolai M. E.; Ueberück, Maximilian; Meißner, Julius N.; Pelgrim, Charlotte E.; Adams, Johnathan; Wirths, Oliver; Bouter, Yvonne; Bayer, Thomas A. (Frontiers in Aging Neuroscience, 2018)
The N-terminally truncated pyroglutamate Aβ3-42 (AβpE3-42) and Aβ4-42 peptides are known to be highly abundant in the brain of Alzheimer’s disease (AD) patients. Both peptides show enhanced aggregation and neurotoxicity in comparison to full-length Aβ, suggesting that these amyloid peptides may play an important role in the pathogenesis of AD. The aim of the present work was to study the direct effect of the combination of AβpE3-42 and Aβ4-42 on ongoing AD-related neuron loss, pathology and neurological deficits in transgenic mice. Bigenic mice were generated by crossing the established TBA42 and Tg4-42 mouse models expressing the N-truncated Aβ peptides AβpE3-42 and Aβ4-42, respectively. After generation of the bigenic mice, detailed phenotypical characterization was performed using either immunostainings to evaluate amyloid pathology or quantification of neuron numbers using design-based stereology. The elevated plus maze was used to study anxiety levels. In order to evaluate sensori-motor deficits, the inverted grid, the balance beam and the string suspension tasks were applied. We could demonstrate that co-expression of AβpE3-42 and Aβ4-42 accelerates neuron loss in the CA1 pyramidal layer of young bigenic mice as seen by reduced neuron numbers in comparison to single transgenic homozygous mice expressing either AβpE3-42 or Aβ4-42. This observation coincides with the robust intraneuronal Aβ accumulation observed in the bigenic mice. In addition, loss of anxiety and motor deficits were enhanced in an age-dependent manner. The sensori-motor deficits correlate with the abundant spinal cord pathology, as demonstrated by robust intracellular Aβ accumulation within motor neurons and extracellular Aβ deposition. Our observations demonstrate that a combination of AβpE3-42 and Aβ4-42 has a stronger effect on ongoing AD pathology than the peptides alone. Therefore, AβpE3-42 and Aβ4-42 might represent excellent potential therapeutic targets and diagnostic markers for AD.